Investigating the Potential Beneficial Effects of Native Banana Starch on Glycemia and Insulin Resistance in Obese Non-Diabetic Women - Ble-Castillo, Jorge Luis; Aparicio-Trápala, María A.; Gómez-Vázquez, Armando; Rodríguez-Hernández, Arturo; Mendez, José D.; Juárez-Rojop, Isela E.; Aguilar-Mariscal, Hidemí; Díaz-Zagoya, Juan C. (Issues and Development in Health Research Vol. 2, 2021)
Several studies have shown that life-style changes can help reduce the risk of diabetes. The purpose of this study was to assess the effects of native banana starch (NBS) on glycemic control and insulin resistance in comparison with metformin (MF) in non-diabetic obese women. Forty participants 20-45 years of age, HOMA- IR \(\ge\)2.5 were randomly assigned to two groups of 20 subjects each. During an eight-week period, one group received NBS 30g/day and the other MF 850 mg/day. Fasting glycemia was reduced by either four weeks NBS or four weeks MF treat-ment (week 0 vs week 4, p<0.05). After NBS and MF treatments, fasting insulin and HOMA-IR values decreased gradually, reaching statistical significance after eight weeks (week 0 vs week 8, p<-0.05). The 30 and 60min insulin AUCs after eight weeks NBS supplementation tended to be lower in comparison to 30 and 60min insulin AUCs at baseline. There were no differences in HOMA-IR response between treatments after four or eight weeks. Data show that NBS supplementation has beneficial effects in reducing fasting glucose and insulin resistance in a group of obese women, and it may represent a low-cost and easily accessible alternative for preventing complications in the obese population.